2008
DOI: 10.1016/j.yexcr.2008.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule (NCAM) marks adult myogenic cells committed to differentiation

Abstract: Although recent advances in broad-scale gene expression analysis have dramatically increased our knowledge of the repertoire of mRNAs present in multiple cell types, it has become increasingly clear that examination of the expression, localization, and associations of the encoded proteins will be critical for determining their functional significance. In particular, many signaling receptors, transducers, and effectors have been proposed to act in higher-order complexes associated with physically distinct areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 69 publications
(85 reference statements)
0
80
0
2
Order By: Relevance
“…Therefore, in the reorganisation that occurs during cell differentiation processes, adhesion molecules are involved [66]. We found Vcam1 and Ncam-180 up-regulated, both of which code for cell adhesion molecules and which contribute to myotube formation through fusion of myoblasts [39,40]. Some studies have shown that for C2C12 myoblasts [67], Ncam expression is associated with the early stages of differentiation, and is concurrent with expression of T-type Ca 2+ channels and inward rectifier K + channels [68].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, in the reorganisation that occurs during cell differentiation processes, adhesion molecules are involved [66]. We found Vcam1 and Ncam-180 up-regulated, both of which code for cell adhesion molecules and which contribute to myotube formation through fusion of myoblasts [39,40]. Some studies have shown that for C2C12 myoblasts [67], Ncam expression is associated with the early stages of differentiation, and is concurrent with expression of T-type Ca 2+ channels and inward rectifier K + channels [68].…”
Section: Discussionmentioning
confidence: 78%
“…It is an intracellular protein that associates with cadherins and the cytoskeleton, and it is required for the formation and maintenance of functional intercellular adhesion complex. Neuronal cell adhesion molecule (ncam)-180 was up-regulated at 4 and 24 h of differentiation, and a predominant trend for upregulation was observed for vascular cell adhesion molecule 1 at both times; both of these code for cell adhesion molecules that are expressed on the surface of skeletal muscle satellite cells, and which contribute to myotube formation through the fusion of myoblasts [39,40]. Cell adhesion is a process that is highly correlated to myoblast fusion and myogenesis.…”
Section: Cell Adhesionmentioning
confidence: 99%
“…Adult mouse myoblasts were isolated from wild-type (B6D2F1, Jackson Labs), CBA gfp (Jackson Labs), or ROSA mTmG (Jackson Labs) female mice by our published methods (Capkovic et al, 2008). Briefly, mice were euthanized, hindlimbs removed and skinned, and muscles removed in PBS.…”
Section: Muscle Satellite Cell Isolation and Culturementioning
confidence: 99%
“…NCAM was the first marker used to identify human muscle satellite cells, and this marker is expressed in satellite cells, myoblasts, myotubes and muscle fibers during development (Boldrin et al, 2010). This marker is expressed in proliferating human and rat muscle cells, but is not a reliable marker in mice muscle cells; mice muscle cells express NCAM only when they have become committed to differentiation (Capkovic et al, 2008). We observed that NCAM is expressed in proliferating cells from bovine muscle.…”
Section: Discussionmentioning
confidence: 78%
“…Likewise, differences are also observed between primary cell model systems from different species. The neural cell adhesion marker (NCAM) is expressed in proliferating human and rat cells (Boldrin et al, 2010), but not in mice muscle cells (Capkovic et al, 2008). Cattle are evolutionary closer to humans than rodents, and the entire bovine genome is fully sequenced in order to provide an important supplement for human medical research (Tellam et al, 2009).…”
Section: Introductionmentioning
confidence: 99%